THE INFLUENCE OF BASAL PROCESSES ON THE DYNAMIC BEHAVIOUR OF COLD-BASED GLACIERS - Waller R.I. (My University, 2001)
There exists within glaciology a widely held assumption that basal sliding and bed deformation do not operate beneath cold-based ice and that their basal velocity is therefore zero, irrespective of bed conditions. Consequently, their ability to erode, entrain and transport sediment and thereby alter the landscape is assumed to be limited. Consequently, very little research has been focused towards describing and understanding the motion of cold-based ice-masses and our knowledge of their behaviour remains poor and the assumption of zero basal velocity, unchallenged.In this review paper, it is argued that this assumption is not universally applicable and that in certain circumstances, basal processes not only remain active at sub-freezing temperatures, but can significantly influence glacier motion. This is particularly the case in glaciers where sub-freezing basal thermal conditions coincide with the presence of fine grained, ice-rich subglacial sediments. Due to the lack of work undertaken on contemporary cold-based glaciers, much of the information used to support this argument is derived from field research in permafrost areas and on Quaternary glacial sediments, and from the laboratory testing of ice/sediment mixtures.It is concluded that the assumption of zero basal velocity beneath cold-based ice is overly simplistic and that in reality, the situation is likely to be much more complex. Work is therefore urgently required: firstly, to investigate the circumstances in which basal motion remains active at sub-freezing temperatures and to determine their influence on glacier motion and; secondly, to examine the likely extent of subglacial permafrost in both the contemporary and Quaternary glacial environment.
Keywords: Quaternary; Cenozoic::Quaternary; Кайнозой::Четвертичная